Strategy for the Development of Islamic Educational Institutions at the Muhammadiyah Grobogan Institute of Business Technology - Fitria Nita Witanti; Fauzi Muharom; Toto Suharto (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2025)
Islamic education institutions within Muhammadiyah Universities (PTM) play a strategic role in maintaining and developing Islamic values and the Muhammadiyah ideology within the academic environment. However, these institutions face various internal challenges, such as limited human resources and program innovation, as well as external challenges in the form of digital disruption, secularization of values, and changes in student characteristics. This study aims to examine the importance of strategic management in the development of Islamic education institutions in PTM using a descriptive qualitative approach. The results showed that the implementation of strategic management through the stages of strategy formulation, implementation, and evaluation can increase the effectiveness, relevance, and sustainability of the institution. Identification of strengths, weaknesses, opportunities, and threats (SWOT) and the use of the Balanced Scorecard approach are proven to help design policies and programs that are more measurable and impactful. This study recommends the need for visionary leadership, cross-unit collaboration, and strengthening Islamic values-based governance in realizing a superior and competitive institution amid the dynamics of higher education.